Enhancing liquid droplet breakup by hydrophobic wire mesh: Visual study and application in a rotating packed bed. (14th December 2019) - Zhang, Jing-Peng; Liu, Wei; Luo, Yong; Chu, Guang-Wen; Zou, Hai-Kui; Chen, Jian-Feng
Graphical abstract: Highlights: Different liquid droplet breakup regimes were studied by using a high-speed camera. The mean daughter droplet diameter obtained by SSM was smaller than that by NSM. Smaller dissipation energy of SSM resulted in more energy for mother droplet breakup. SSM could be an effective internal for mass transfer intensification in a RPB. Abstract: Liquid droplet breakup significantly affects the mass transfer performance in chemical reactors. For example, in a rotating packed bed (RPB) reactor, several studies focused on the structure innovations of packing and rotor to enhance liquid droplet breakup. However, using the surface-modification packing with hydrophobicity to intensify the liquid droplet breakup has scarcely been assessed. In this work, a hydrophobic surface-modified stainless steel wire mesh (SSM) was employed to investigate the breakup behaviors of liquid droplet when the mother droplet passed through a single-layer SSM by using a high-speed camera. Different regimes were observed when the mother droplet passed through the single-layer SSM and non-surface-modified stainless steel wire mesh (NSM). The mean daughter droplet diameter obtained by SSM was smaller than that by NSM. Correlations of the mean daughter droplet diameters were proposed, and the predicted values were in a good agreement with the experimental values, having a deviation of ±15%. Experimental and modeling results showed smaller dissipation energy of SSM resulted in more energy for mother droplet breakup. Due to the droplet breakup enhancement, the mass transfer performance of a RPB with SSM loaded in the cavity zone was intensified.